2017
DOI: 10.2147/dddt.s126964
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces apoptosis and protective autophagy in castration-resistant prostate cancer cells through iron chelation

Abstract: BackgroundCurcumin induces apoptosis and autophagy in different cancer cells. Moreover, chemical and biological experiments have evidenced that curcumin is a biologically active iron chelator and induces cytotoxicity through iron chelation. We thus hypothesized that curcumin may induce apoptosis and autophagy in castration-resistant prostate cancer (CRPC) cells through its iron-chelating properties.Materials and methodsCRPC cells were loaded with curcumin alone or in combination with ferric ammonium citrate (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…Total protein samples were extracted from the cultured cells using an radioimmunoprecipitation assay buffer (Beijing Solarbio Science & Technology Co., Ltd., Beijing, China) according to the manufacturer's protocol. Immunoblotting was performed as previously described (8). The primary antibodies, including anti-p62 (cat.…”
Section: Transient Transfection With Green Fluorescence Protein (Gfp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Total protein samples were extracted from the cultured cells using an radioimmunoprecipitation assay buffer (Beijing Solarbio Science & Technology Co., Ltd., Beijing, China) according to the manufacturer's protocol. Immunoblotting was performed as previously described (8). The primary antibodies, including anti-p62 (cat.…”
Section: Transient Transfection With Green Fluorescence Protein (Gfp)mentioning
confidence: 99%
“…When autophagy is initiated, cytosolic light chain (LC)3 (LC3-I) loses a small polypeptide during enzymatic hydrolysis and is transformed into the membrane type of LC3, LC3-II, thereby enhancing the formation of an autophagosome. Thus, the LC3I/LC3II ratio may be utilized to estimate the level of autophagy (8). Clinical studies have demonstrated that autophagy is enhanced after cancer therapy, and is therefore involved in the development of chemotherapy resistance (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…It suggests that curcumin may serve as a promising anticancer agent by inducing a chronic endoplasmic reticulum (ER) stress mediated cell death and activation of cell cycle arrest, unfolded protein response, autophagy, and oxidative stress responses . In addition, curcumin induces apoptosis and protective autophagy in castration‐resistant prostate cancer cells, which are at least partially dependent on its iron‐chelating properties . In our study, curcumin inhibits growth of prostate cancer in vivo and also promotes apoptosis of LNCaP cells in vitro.…”
Section: Discussionmentioning
confidence: 57%
“…Curcumin was reported to play a protective role in the prostate cancer . However, the epigenetic molecular mechanism of curcumin in cancer has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications show that curcumin is involved in mitochondrial destabilization (8,25) and induces mitochondrial biogenesis (26). Hypothetically, if curcumin treatment increases the ratio of Bax/Bcl-2 or results in a leaky mitochondrial membrane, curcumin could be linked to mitochondrial destabilization, apoptosis, and mitophagy (8,18,27). But this hypothesis does not need a direct interaction between curcumin and the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%